Synthesis and Characterization of Activated Carbon from Waste Compedak Fruit (Artocarpus Champeden) Activated H3PO4 as Adsorbent of Methylene Blue - Catherina Bijang; Matheis F. J. D. P. Tanasale; Dewi Sri; Tahril Tahril; Thamrin Azis (Universitas Tadulako, 2022)
Synthesis of activated carbon from cempedak peel waste is carried out to utilize biomass waste. This study aimed to synthesize and characterize activated carbon from cempedak peel waste. The synthesis was carried out by chemical activation using phosphoric acid with a dry impregnation ratio of 1:4 (g sample:g H3PO4). Samples impregnated for 24 hours were then heated at 250℃—and then calcined at 350℃ and 450℃. The XRD and FTIR characterization results indicated that the activated carbon obtained had an amorphous structure and the activated carbon obtained had hydroxyl, carbonyl, and carboxylic groups. Activated carbon with the highest yield was obtained at a temperature of 350, namely 43%. The results of determining the water content of activated carbon obtained are 8.36% at 350 0C and 7.1% at 450 ℃. The value of water content and ash content of activated carbon from the skin of this cempedak fruit has met the Indonesian National Standard (SNI 06-3730-1995). The best-activated carbon yield was at a calcination temperature of 450, with the percentage of adsorption efficiency on methylene blue of 98.88%.